'Fukusensor:' a genetically engineered plant for reporting DNA damage in response to gamma radiation. Issue 9 (4th September 2014) - Peng, Yanhui; Allen, Sara; Millwood, Reginald J.; Stewart, C. Neal
Summary Transgenic plants can be designed to be 'phytosensors' for detection of environmental contaminants and pathogens. In this study, we describe the design and testing of a radiation phytosensor in the form of green fluorescence protein (GFP)‐transgenic Arabidopsis plant utilizing a DNA repair deficiency mutant background as a host. Mutant lines of Arabidopsis AtATM (At3g48190), which are hypersensitive to gamma irradiation, were used to generate stable GFP transgenic plants in which a gfp gene was under the control of a strong constitutive CaMV 35S promoter. Mutant and nonmutant genetic background transgenic plants were treated with 0, 1, 5, 10 and 100 Gy radiation doses, respectively, using a Co‐60 source. After 1 week, the GFP expression levels were drastically reduced in young leaves of mutant background plants (treated by 10 and 100 Gy), whereas there were scant visible differences in the fluorescence of the nonmutant background plants. These early results indicate that transgenic plants could serve in a relevant sensor system to report radiation dose and the biological effects to organisms in response to radionuclide contamination.